An intelligent oil reservoir identification approach by deploying quantum Levenberg-Marquardt neural network and rough set. (14th July 2011) - Liu, Nanping; Zheng, Fei; Xia, Kewen
An intelligent identification approach combining the features of parallel computation of quantum Levenberg-Marquardt neural network (Q-LM-NN) and information reduct of rough set is proposed as an improved alternative to common statistical identification methods and single-intelligent-based methods which are unable to attain satisfactory result in engineering applications. This approach has been tested to have better performance on reducing the cost and improving the identification accuracy than other methods in practical oil log applications.